2009
DOI: 10.2174/1874312900802010089
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcome in Systemic Lupus Erythematosus (SLE) is Improving: Results from a Case Control Study and Literature Review

Abstract: Abstract:Objectives: For women who suffer from systemic lupus erythematosus (SLE), pregnancy can be a concern, placing the mother and fetus at risk. Our objectives were to assess the risk of adverse pregnancy outcome, disease flares, fertility rate, and co-morbidities in SLE women compared to healthy controls. We also systematically reviewed the literature available on pregnancy outcome in SLE to compare our results to other published data. Our hypothesis was that pregnancy outcome in SLE is improving over tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
77
3
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 81 publications
10
77
3
5
Order By: Relevance
“…As mentioned above, prior studies have shown that women with SLE are at an increased risk of certain placenta-mediated pregnancy complications (e.g., preeclampsia, late pregnancy loss, and SGA) (1,2). Anomalies in placental pathology are commonly found in women with SLE (both in the presence and absence of antiphospholipid antibodies [aPL]), including frequent hypoxicischemic change, decidual vasculopathy, and lower-thanexpected placental weight (for gestational age).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, prior studies have shown that women with SLE are at an increased risk of certain placenta-mediated pregnancy complications (e.g., preeclampsia, late pregnancy loss, and SGA) (1,2). Anomalies in placental pathology are commonly found in women with SLE (both in the presence and absence of antiphospholipid antibodies [aPL]), including frequent hypoxicischemic change, decidual vasculopathy, and lower-thanexpected placental weight (for gestational age).…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies of pregnant women with SLE, most retrospective in design and including a limited number of subjects, have shown a wide-ranging prevalence of stillbirths, with estimates between 1% and 3% (1). In addition, these studies have mainly been conducted in tertiary care centers, and have not directly compared stillbirths occurring in women with SLE to a general population control group.…”
mentioning
confidence: 99%
“…22 Maternal lupus activity and the presence of antiphospholipid antibodies were associated with concomitant major causes of obstetric complications, 12,22 It is estimated that approximately 20% of pregnancies in women with SLE result in fetal loss. 23 The rate of preterm birth (birth before 37 weeks gestation) is also increased in this group of patients. The incidence appears to vary between 23% and 28%.…”
Section: Discussionmentioning
confidence: 76%
“…The incidence appears to vary between 23% and 28%. 23 Preterm birth is often spontaneous, and it is mainly due to premature rupture of membranes, but there is also a significant portion of cases in which labor is induced to protect the health of mother and / or baby (early fetal distress or preeclampsia). 19 In relation to serum markers of hereditary thrombophilia, protein C deficiency, S and antithrombin, we found an incidence of 40% (10/25) among pregnant women with lupus, however several authors, 9,24,25 did not find the presence of these markers in non-pregnant patients with SLE, suggesting that they were not associated with an increased thrombotic risk.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy can exacerbate lupus, and can even be life-threatening to mother and child. [5][6][7][8][9][10][11] In this study, we aimed to analyze the relationship between pregnancy and lupus, and explore the risk factors that adversely affect maternal and infant outcomes.…”
mentioning
confidence: 99%